Introducing Indonesian Culture through Educative Boardgame Using Augmented Reality: A Prototype of Grand Indonesia Java Edition Boardgame - Daniel Kurniawan Salamoon; Gabriella Angeline; Amadeus Jacaranda; Bryant Pasadeva (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2023)
The use of digital media in education is a necessity nowadays. This is also an effect due to conditions of Covid-19 pandemic. Although there is a stigma that digital media has an unfavorable impact on the student learning process, technological developments also support creative concepts that can be used at the educational level. Based on these conditions, the idea emerged to develop an educational media based on boardgames to provide a learning process. In this study, researchers chose a general topic as the basis for the content of the boardgame, which is Indonesian culture. This topic was chosen considering the need for the younger generation to understand about Indonesian culture as their homeland. The research method in finding content is collecting data about Indonesian culture from books and the internet. While the design development uses qualitative methods as the basis for thinking. In this development, the resulting prototype is a combination of designs on paper and the use of smartphones in the explanation process using Augmented Reality technology. It is hoped that this prototype can become a design that attracts the interest of the younger generation to learn about their own culture.